State Medicaid fees and access to primary care physicians. (24th September 2017) - Sharma, Rajiv; Tinkler, Sarah; Mitra, Arnab; Pal, Sudeshna; Susu‐Mago, Raven; Stano, Miron
Abstract: Medicaid and uninsured patients are disadvantaged in access to care and are disproportionately Black and Hispanic. Using a national audit of primary care physicians, we examine the relationship between state Medicaid fees for primary care services and access for Medicaid, Medicare, uninsured, and privately insured patients who differ by race/ethnicity and sex. We found that states with higher Medicaid fees had higher probabilities of appointment offers and shorter wait times for Medicaid patients, and lower probabilities of appointment offers and longer wait times for uninsured patients. Appointment offers and wait times for Medicare and privately insured patients were unaffected by Medicaid fees. At mean state Medicaid fees, our analysis predicts a 27‐percentage‐point disadvantage for Medicaid versus Medicare in appointment offers. This decreases to 6 percentage points when Medicaid and Medicare fees are equal, suggesting that permanent fee parity with Medicare could eliminate most of the disparity in appointment offers for Medicaid patients. The predicted decrease in the disparity is smaller for Black and Hispanic patients than for White patients. Our research highlights the importance of considering the effects of policy on nontarget patient groups, and the consequences of seemingly race‐neutral policies on racial/ethnic and sex‐based disparities.